Annual Plan 1974-75 - Planning Commission (Planning Commission, 1974)
The Annual Plan 1974-75 marks the beginning of the Fifth Five Year Plan (1974-79) which constitutes another important landmark in the history of planned economic and social development of the country. Its formulation has, however, coincided with a difficult phase through which the economy has been passing because of both internal and external developments. The Annual Plan 1974-75 has, therefore, been formulated in the background of current economic situation and within the framework of the Draft Fifth Five Year Plan. Review of Current Economic Situation 2. The economy has been under severe strain for some time past. There has been a sharp increase in the prices since May, 1972. Shortages of essential consumer goods and critical raw materials have been a persistent feature over the last two years.
Government of India Planning Commission